Martensitic transformation and giant magnetic entropy change in Ni42.8Mn40.3Co5.7Sn11.2 alloy - 陈峰华 宫长伟 郭艳萍 张敏刚 柴跃生 (中国物理B：英文版, 2014)
The crystal structure, phase transition, and magnetocaloric effect in Ni42.8Mn40.3Co5.7Sn11.2 alloy are investigated by structure analysis and magnetic measurements. A large magnetic entropy change of 45.6 J/kg.K is obtained at 215 K under a magnetic field of 30 kOe （1 Oe = 79.5775 A.m-1）. The effective refrigerant capacity of Ni42.8Mn40.3Co5.7Sn11.2 alloy reaches 72.1 J/kg under an applied field changing from 0 to 30 kOe. The external magnetic field shifts the martensitic transition temperature about 3-4 K/10 kOe towards low temperature, indicating that magnetic field can retard the phase transition to a certain extent. The origin of large magnetic entropy change is discussed in the paper.